Breeding for bruchid resistance in cowpea - Singh, B.B.; Singh, S.R. (Springer, 1990)
One of the most important constraints in cowpea storage is widespread infestation by the seed beetle, Callosobruchus maculatus (F.), commonly known as bruchid. In addition to causing direct seed weight loss, it reduces seed quality and also affects germination. The International Institute of Tropical Agriculture (IITA) initiated a systematic program in 1974 to develop bruchid resistant cowpea varieties and TVu 2027 was identified as moderately resistant. During the last several years, over 8,000 germplasm accessions have been screened and few additional sources have been identified. The resistance is characterized by delayed, staggered and lower emergence levels of bruchids. Therefore resistant accessions suffer less damage than susceptible ones. On average, within a storage period of 100 days, the resistant accessions show about 25% damaged seeds compared to 95% for the susceptible varieties. The genetics of resistance has been studied and resistance is incorporated in advance breeding lines at IITA. IT84S-2246-4 is one of the superior lines which apart from resistance to bruchid, combines resistance to other pests; aphids, thrips along with resistance to 10 diseases. This line appears to perform well in Nigeria and is being used as an important parent. Because bruchid resistance in cowpea is controlled by 2 pairs of recessive genes, any outcrossing reduces the proportion of resistant plants in succeeding generations. Its implication in germplasm collection and varietal maintenance is discussed.